Cervical spinal cord ischemia – flaccid tetraplegia as a complication after partial resection of the trachea - Majchrzak, Maciej; Gietkiewicz, Krzysztof; Kołodziej, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
In the following article we present the case report of a cervical spinal cord ischemia with flaccid tetraplegia after partial resection of the trachea in an 26-year old patient.